Polyacrylate modified recycled concrete and preparation method thereof

Through vacuum saturated water treatment and low water-cement ratio polymer cement slurry shell technology, the problem of difficult to fill in microcracks and micropores of recycled concrete is solved, significantly improving its strength and durability, making it have a higher service life in harsh environments.

CN116283107BActive Publication Date: 2025-04-25NANTONG ACADEMY OF BUILDING RES
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202310380592.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-04-11
Publication Date
2025-04-25
Estimated Expiration
2043-04-11

AI Technical Summary

Technical Problem

Recycled concrete is difficult to fill with the microcracks and micropores on the surface and interior of the surface and interior, resulting in low strength, low elastic modulus, poor crack resistance and poor durability, which limits its application in actual engineering.

Method used

The microcracks and micropores inside the regenerated aggregate are filled by vacuum saturated water treatment, and the polymer cement slurry shell with low water-cement ratio and polyacet ratio is exchanged with the residual water film on the surface of the coarse aggregate and free water in the microcracks to improve the interface relationship between the coarse aggregate and cement stone, and the mechanical properties of concrete are enhanced through secondary shell formation.

Benefits of technology

The strength, crack resistance and durability of recycled concrete has been significantly improved, making it have a higher service life in harsh areas such as frozen and thawing climate, marine engineering and saline-alkali environment. Compared with ordinary concrete and recycled aggregate concrete, the service life of polyacrylate modified recycled concrete is 17.0 years and 19.6 years higher, respectively.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116283107B_ABST
    Figure CN116283107B_ABST
Patent Text Reader

Abstract

The invention relates to the field of civil engineering, and discloses a polyacrylate modified recycled concrete and a preparation method thereof, comprising 170-200 parts of mixing water, 350-500 parts of cement, 500-800 parts of fine aggregate, 300-500 parts of recycled coarse aggregate with a particle size of 5-10 mm, 500-800 parts of recycled coarse aggregate with a particle size of 10-20 mm, 35-55 parts of polyacrylate emulsion, 1-5 parts of polyacrylonitrile fiber, 1-5 parts of high-performance water reducer, and 1-3 parts of defoamer. The recycled aggregate is treated by soaking the recycled aggregate for standby use, mixing the mixing water, the polyacrylate emulsion and the organosilicon defoamer, mixing the polyacrylonitrile fiber, sand and cement in proportion, draining the recycled aggregate, putting the cement and the mixed liquid in the proportion into a mixer, stirring, stopping the mixer, putting the recycled coarse aggregate into the mixer, stirring, stopping the mixer, putting the mixed dry material into the mixer, stirring, stopping the mixer, putting the water reducer and the mixed liquid into the mixer, stirring, stopping the mixer, and discharging the material. The relative dynamic elastic modulus loss rate, mass loss rate, compressive strength loss rate and flexural strength loss rate of the concrete of the present invention are superior to those of ordinary natural aggregate concrete and ordinary recycled aggregate concrete.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of civil engineering, and in particular to polyacrylate modified recycled concrete and a preparation method thereof. Background Art

[0002] With the progress of urbanization in my country in the new era, old buildings have been gradually demolished, and a large amount of construction waste has been generated in this process. At the same time, the rapid infrastructure construction has consumed huge natural building material resources. At present, the prices of various building materials have risen sharply, and the problem of resource depletion is becoming increasingly serious. Before this, the main way to deal with construction waste in my country was landfill, which not only occupied a large amount of land, but also caused serious environmental pollution. Therefore, the reuse of construction waste is of great significance. Recycled concrete that uses recycled aggregates to replace natural aggregates is a green building resource. However, compared with natural aggregate concrete, recycled concrete has the disadvantages of low strength, low elastic modulus, poor crack resistance and poor durability, which limits the application of recycled concrete in actual engineering.

[0003] Since recycled aggregates are crushed and screened from construction waste, there are many micro cracks and micro pores on their surface and inside. Under the conventional mixing procedure, these cracks and pores are difficult to be filled by mixing water. They will exist in the recycled concrete for a long time, becoming permanent defects and a hidden danger of cracking and damage of concrete components during use. In the traditional one-time mixing method, the presence of water film on the surface of coarse aggregate can easily cause poor interface between the coarse aggregate surface and cement stone, and low interface strength.

[0004] In the field of concrete materials, people today not only pursue green environmental protection concepts, but also put forward higher requirements for material performance. In order to improve the utilization rate of construction waste, promote the further development of green buildings, and reduce the adverse effects of construction waste concrete on the natural environment.

[0005] In the document CN 110713361 A, a high-performance concrete containing recycled aggregate and its preparation method are disclosed. Each cubic meter of antifreeze concrete is composed of the following raw materials in the following proportions: 260-350 kg of water, 480-500 kg of cement, 120-150 kg of recycled coarse aggregate, 450-550 kg of fine aggregate, 400-500 kg of slag powder, 480-560 kg of coal slag powder, 6-9 kg of polyacrylate, 4-5 kg ​​of heavy calcium powder, and 60-90 g of corundum. The preparation method is as follows: step 1, weighing the raw materials according to the above proportions; step 2, pouring the raw materials except polyacrylate in step 1 into a concrete mixer and stirring for 100s-120s; step 3, pouring polyacrylate into a mixer and stirring for 100s-150s; step 4, manually stirring the mixture obtained in step 3. Although it is also a method for preparing recycled aggregate concrete, the mixing process for repairing the surface defects of the recycled aggregate is not used during the production, and the interface relationship between the coarse aggregate and the cement stone is not improved. Therefore, it is very easy to cause low interface strength and poor concrete performance. Summary of the invention

[0006] In order to solve the above problems, the present invention discloses a polyacrylate-modified recycled concrete and a preparation method thereof. In the field of concrete materials, people today not only pursue green environmental protection concepts, but also put forward higher requirements for material performance. In order to improve the utilization rate of construction waste, promote the further development of green buildings, and reduce the adverse effects of construction waste concrete on the natural environment, the application of the polyacrylate-modified recycled concrete of the present invention can not only make the construction project more green and environmentally friendly, but also is a high-performance concrete suitable for areas with harsh natural conditions such as freeze-thaw climate, marine engineering, and saline-alkali environment. According to calculations, the service life of the polyacrylate-modified recycled concrete of the present invention in areas with severe salt-freeze erosion such as Southwest, Northwest, North China, and Northeast my country is 17.0 years higher than that of ordinary concrete on average, and 19.6 years higher than that of ordinary recycled aggregate concrete on average, so it has long-term practical significance.

[0007] The technical solution of the present invention is: polyacrylate modified recycled concrete, comprising the following components in parts by weight:

[0008] Mix 170-200 parts of water;

[0009] 350-500 parts of cement;

[0010] 500-800 parts of fine aggregate;

[0011] 300-500 parts of recycled coarse aggregate with a particle size of 5-10 mm;

[0012] 500-800 parts of recycled coarse aggregate with a particle size of 10-20 mm;

[0013] Polyacrylate emulsion 35-55 parts;

[0014] 1-5 parts of polyacrylonitrile fiber;

[0015] 1-5 parts of high performance water reducing agent;

[0016] 1-3 parts of defoaming agent.

[0017] Preferably, the dry matter in the polyacrylate emulsion is 15-25 parts, and the water contained in the polyacrylate emulsion should be included in the total water consumption.

[0018] Preferably, the fine aggregate is natural medium sand of zone II with a fineness modulus of 2.5; the recycled coarse aggregate used is continuously graded, and the raw material is waste concrete.

[0019] The method for preparing polyacrylate-modified recycled concrete comprises the following steps:

[0020] Step 1: Vacuum saturation treatment of recycled aggregate, the steps are as follows:

[0021] Step a: Put the recycled aggregate into a sealable container with a vacuum pump and a water injection pipe;

[0022] Step b: Start the vacuum pump, reduce the absolute pressure in the container to 1-5 kPa within 10-15 minutes and maintain the vacuum for 3-4 hours;

[0023] Step c: While maintaining the vacuum, inject mixing water into the container. The mixing water should completely submerge the recycled aggregate;

[0024] Step d: After the recycled aggregate is submerged in the mixing water, the vacuum is maintained for 1-2 hours, and then normal pressure can be restored and the immersion is continued for no less than 18 hours;

[0025] Step e: soaking the recycled aggregate after vacuum saturation treatment in mixing water for later use;

[0026] By adopting the above technical solution, the micro cracks and micro pores are filled with mixing water after vacuum saturation treatment. In the subsequent mixing step, due to the effect of osmotic pressure, the cementitious material (cement) and polyacrylate will smoothly enter these cracks and pores, thereby facilitating the filling and repair of the above micro cracks and micro pores.

[0027] Step 2: Mix all the mixing water, polyacrylate emulsion and silicone defoamer according to the above-mentioned proportion, stir evenly by mechanical or manual means to prepare a mixed solution for standby use;

[0028] Step 3: Mix all the polyacrylonitrile fibers, all the sand and 45-50% of cement according to the above-mentioned mix ratio, and dry-mix them evenly by mechanical or manual means to prepare a mixed dry material for standby use;

[0029] By adopting the above technical solution, on the one hand, preparation is made for the subsequent secondary shell making of recycled coarse aggregate; on the other hand, in order to prevent the polyacrylonitrile fiber from agglomerating and unevenly dispersing during the wet mixing process, dry mixing is used in advance for dispersion treatment;

[0030] Step 4: Take out the recycled aggregate pretreated in step 1 from the water, drain it, weigh it according to the above mix ratio, and immediately proceed to the next step of preparing polyacrylate-modified recycled concrete after weighing;

[0031] Step 5: Weigh 50-55% of the cement according to the above mix ratio and put it into the forced mixer, and weigh 40-45% of the mixed solution prepared in step 2, put it into the mixer, stir, stop the mixer, and then put all the recycled coarse aggregate weighed in step 4, continue stirring, and stop;

[0032] By adopting the above technical scheme, the recycled coarse aggregate is wrapped with a polymer cement paste with a low water-cement ratio and a polymer-cement ratio. The polymer cement paste shell with a low water-cement ratio and a polymer-cement ratio will exchange substances with the residual water film on the surface of the coarse aggregate and the free water in the microcracks and micropores of the coarse aggregate under the action of osmotic pressure, thereby reducing the influence of the water film on the surface of the coarse aggregate, improving the interface relationship between the coarse aggregate and the cement paste, filling and repairing the surface defects of the coarse aggregate, and making the recycled coarse aggregate more closely combined with the cementitious material and the polymer.

[0033] Step 6: After step 5 is completed and the machine is shut down, all the mixed dry materials obtained in step 3 are immediately put into the mixer, and the machine is shut down after stirring;

[0034] By adopting the above technical scheme, a secondary shell is formed on the basis of the primary shell of the recycled coarse aggregate, i.e., a polymer fiber cement mortar shell. The mixed dry material added on the basis of step (5) further reduces the water-cement ratio and polymer-cement ratio of the primary shell of the recycled coarse aggregate, and the coarse aggregate is more tightly combined. At the same time, the fiber cement mortar added for the second time makes the polyacrylonitrile fiber and the fine aggregate adhere to the primary shell to form a secondary shell. The secondary shell tightly combines the cementitious material with low water-cement ratio and polymer-cement ratio, the fine aggregate and the fiber, which is crucial to the overall mechanical properties and durability of the concrete material in the future.

[0035] Step 7: Mix all the high-performance water-reducing agent weighed according to the above-mentioned mix ratio with the remaining 55-60% of the mixed solution prepared in step 2, stir them evenly by mechanical or manual means, put them into the mixer after stopping the machine in step 6, stir them, and discharge the materials after stopping to obtain the polyacrylate-modified recycled concrete of the present invention.

[0036] Preferably, in step 4, the recycled aggregate is placed on a sieve or a grate for drainage, and the degree of drainage is that the recycled aggregate reaches a saturated surface dry state, that is, weighing is performed when there is no water dripping from the bottom and the surface of the recycled aggregate is not completely dry.

[0037] Preferably, in step 5, 50-55% of the cement weight according to the mix ratio and 40-45% of the mixed solution prepared in step 2 are added to the mixer and stirred at a speed of 47-55 r / min for 60-90 seconds, then stopped, and then the recycled aggregate is added and stirred for 30-50 seconds before stopping.

[0038] By adopting the above technical solution, the influence of water film on the surface of coarse aggregate is reduced, the interface relationship between coarse aggregate and cement paste is improved, the surface defects of coarse aggregate are filled and repaired, and the recycled coarse aggregate is more closely combined with cementitious materials and polymers.

[0039] Preferably, in step 6, immediately after step 5 is completed and the machine is shut down, all the mixed dry materials obtained in step 3 are put into the mixer, stirred at a speed of 47-55 r / min for 30-50s and then shut down.

[0040] Preferably, after the mixer is put into step 7, the mixer is started and stirred at a speed of 47-55 r / min for 120-150 s, and the material is discharged after stopping.

[0041] By adopting the above technical scheme, the rheological properties of the concrete are improved and the working performance is improved in this step, while the impact on the low water-cement ratio and low polymer-cement ratio shell formed by the above-mentioned two shell making processes is minimized, and the polyacrylate-modified recycled concrete of the present invention is prepared.

[0042] The benefits of the present invention are as follows: 1. After the vacuum saturation treatment, the microcracks and micropores of the present invention are filled with mixing water. In the subsequent mixing step, due to the effect of osmotic pressure, the cementitious material (cement) and polyacrylate will smoothly enter these cracks and pores, thereby facilitating the filling and repair of the above-mentioned microcracks and micropores.

[0043] 2. The polymer cement paste shell with low water-cement ratio and polymer-cement ratio of the present invention will exchange substances with the residual water film on the surface of the coarse aggregate and the free water in the microcracks and micropores of the coarse aggregate under the action of osmotic pressure, thereby reducing the influence of the water film on the surface of the coarse aggregate, improving the interface relationship between the coarse aggregate and the cement paste, filling and repairing the surface defects of the coarse aggregate, and making the recycled coarse aggregate more closely combined with the cementitious material and the polymer.

[0044] 3. The present invention performs secondary shelling on the basis of primary shelling of recycled coarse aggregate, i.e., polymer fiber cement mortar shelling. The mixed dry material added on the basis of step (5) further reduces the water-cement ratio and polymer-cement ratio of the primary shell of the recycled coarse aggregate, and makes the shell more tightly bonded with the coarse aggregate. Meanwhile, the fiber cement mortar added for the secondary time makes the polyacrylonitrile fiber and fine aggregate adhere to the primary shell to form a secondary shell. The secondary shell tightly combines the cementitious material with low water-cement ratio and polymer-cement ratio, fine aggregate and fiber, which is crucial to the overall mechanical properties and durability of the concrete material in the future. BRIEF DESCRIPTION OF THE DRAWINGS

[0045] Figure 1 It is a line graph of the relative dynamic elastic modulus change rate in the test results of the present invention;

[0046] Figure 2 It is a line graph of mass change rate in the test results of the present invention;

[0047] Figure 3 is a line graph of compressive strength loss rate in the experimental results of the present invention;

[0048] Figure 4 It is a line graph of the flexural strength loss rate in the experimental results of the present invention. DETAILED DESCRIPTION

[0049] The technical solutions in the embodiments of the invention will be described clearly and completely below in conjunction with the accompanying drawings in the embodiments of the invention.

[0050] Example 1

[0051] Polyacrylate modified recycled concrete, the recycled concrete includes the following components in parts by weight:

[0052] Mixing water 182 parts;

[0053] Cement 418 parts;

[0054] 657 parts of fine aggregate;

[0055] 448 parts of recycled coarse aggregate with a particle size of 5-10 mm;

[0056] 671 parts of recycled coarse aggregate with a particle size of 10-20 mm;

[0057] 41.8 parts of polyacrylate emulsion;

[0058] 1.9 parts of polyacrylonitrile fiber;

[0059] 1.26 parts of high performance water reducing agent;

[0060] 1 part defoamer.

[0061] The dry matter in the emulsion of the polyacrylate emulsion is 18 parts, and the water contained in the polyacrylate emulsion is included in the total water consumption.

[0062] The fine aggregate is natural medium sand in Zone II with a fineness modulus of 2.5; the recycled coarse aggregate used is continuously graded and the raw material is waste concrete.

[0063] The method for preparing polyacrylate-modified recycled concrete comprises the following steps:

[0064] Step 1: Vacuum saturation treatment of recycled aggregate, the steps are as follows:

[0065] Step a: Put the recycled aggregate into a sealable container with a vacuum pump and a water injection pipe;

[0066] Step b: Start the vacuum pump, reduce the absolute pressure in the container to 1 kPa within 15 minutes and maintain the vacuum for 4 hours;

[0067] Step c: While maintaining the vacuum, inject mixing water into the container. The mixing water should completely submerge the recycled aggregate;

[0068] Step d: After the recycled aggregate is submerged in the mixing water, the vacuum is maintained for 1 hour, normal pressure is restored, and the immersion is continued for 20 hours until the polyacrylate-modified recycled concrete begins to be prepared;

[0069] Step e: soaking the recycled aggregate after vacuum saturation treatment in mixing water for later use;

[0070] Step 2: Mix all the mixing water, polyacrylate emulsion and silicone defoamer according to the above-mentioned proportion, stir evenly by mechanical or manual means to prepare a mixed solution for standby use;

[0071] Step 3: Mix all the polyacrylonitrile fibers, all the sand and 50% of the cement according to the above-mentioned mix ratio, and dry-mix them evenly by mechanical or manual means to prepare a mixed dry material for standby use;

[0072] Step 4: Take the recycled aggregate pretreated in step 1 out of the water and place it on a screen or grate for drainage. The degree of drainage is when the recycled aggregate reaches a saturated surface dry state, that is, when there is no water dripping from the bottom and the surface of the recycled aggregate is not completely dry, weigh it according to the above mix ratio, and immediately proceed to the next step of preparing polyacrylate-modified recycled concrete after weighing;

[0073] Step 5: Weigh 50% of the cement according to the above mix ratio and put it into a forced mixer, and weigh 40% of the mixed solution prepared in step 2, put it into the mixer and stir it at a speed of 55r / min for 60s, stir, stop, and then add all the recycled coarse aggregate weighed in step 4, continue stirring for 30s and then stop;

[0074] Step 6: After step 5 is completed and the machine is shut down, all the mixed dry materials prepared in step 3 are immediately put into the mixer, stirred at a speed of 55 r / min for 30 seconds and then stopped;

[0075] Step 7: Mix all the high-performance water-reducing agent weighed according to the above-mentioned mix ratio with the remaining 60% of the mixed solution prepared in step 2, stir them evenly by mechanical or manual means, put them into the mixer after stopping the machine in step 6, start stirring at a speed of 55r / min for 120s, and discharge the materials after stopping the machine to obtain the polyacrylate-modified recycled concrete of the present invention.

[0076] Example 2

[0077] Polyacrylate modified recycled concrete, the recycled concrete includes the following components in parts by weight:

[0078] Mix 195 parts of water;

[0079] 420 parts of cement;

[0080] 660 parts of fine aggregate;

[0081] 435 parts of recycled coarse aggregate with a particle size of 5-10 mm;

[0082] 650 parts of recycled coarse aggregate with a particle size of 10-20 mm;

[0083] 42 parts of polyacrylate emulsion;

[0084] 2 parts of polyacrylonitrile fiber;

[0085] 1.5 parts of high performance water reducing agent;

[0086] 1 part defoamer.

[0087] The dry matter in the emulsion of the polyacrylate emulsion is 18 parts, and the water contained in the polyacrylate emulsion is included in the total water consumption.

[0088] The fine aggregate is natural medium sand in Zone II with a fineness modulus of 2.5; the recycled coarse aggregate used is continuously graded and the raw material is waste concrete.

[0089] The method for preparing polyacrylate-modified recycled concrete comprises the following steps:

[0090] Step 1: Vacuum saturation treatment of recycled aggregate, the steps are as follows:

[0091] Step a: Put the recycled aggregate into a sealable container with a vacuum pump and a water injection pipe;

[0092] Step b: start the vacuum pump, reduce the absolute pressure in the container to 5 kPa within 10 minutes and maintain the vacuum for 4 hours;

[0093] Step c: While maintaining the vacuum, inject mixing water into the container. The mixing water should completely submerge the recycled aggregate;

[0094] Step d: After the recycled aggregate is submerged in the mixing water, the vacuum is maintained for 2 hours, normal pressure is restored, and the immersion is continued for 24 hours until the polyacrylate-modified recycled concrete begins to be prepared;

[0095] Step e: soaking the recycled aggregate after vacuum saturation treatment in mixing water for later use;

[0096] Step 2: Mix all the mixing water, polyacrylate emulsion and silicone defoamer according to the above-mentioned proportion, stir evenly by mechanical or manual means to prepare a mixed solution for standby use;

[0097] Step 3: Mix all the polyacrylonitrile fibers, all the sand and 45% of cement according to the above-mentioned mix ratio, and dry-mix them evenly by mechanical or manual means to prepare a mixed dry material for standby use;

[0098] Step 4: Take the recycled aggregate pretreated in step 1 out of the water and place it on a screen or grate for drainage. The degree of drainage is when the recycled aggregate reaches a saturated surface dry state, that is, when there is no water dripping from the bottom and the surface of the recycled aggregate is not completely dry, weigh it according to the above mix ratio, and immediately proceed to the next step of preparing polyacrylate-modified recycled concrete after weighing;

[0099] Step 5: Weigh 55% of the cement according to the above mix ratio and put it into the forced mixer, and weigh 45% of the mixed solution prepared in step 2, put it into the mixer and stir it at a speed of 50r / min for 70s, stop the mixer, and then add all the recycled coarse aggregate weighed in step 4, continue stirring for 30s and then stop;

[0100] Step 6: After step 5 is completed and the machine is shut down, all the mixed dry materials prepared in step 3 are immediately put into the mixer, stirred at a speed of 50r / min for 30s and then shut down;

[0101] Step 7: Mix all the high-performance water-reducing agent weighed according to the above-mentioned mix ratio with the remaining 55% of the mixed solution prepared in step 2, stir them evenly by mechanical or manual means, put them into the mixer after stopping the machine in step 6, stir them, stop the machine and discharge the materials to obtain the polyacrylate modified recycled concrete of the present invention.

[0102] Example 3

[0103] Polyacrylate modified recycled concrete, the recycled concrete includes the following components in parts by weight:

[0104] Mix 180 parts of water;

[0105] 420 parts of cement;

[0106] 670 parts of fine aggregate;

[0107] 450 parts of recycled coarse aggregate with a particle size of 5-10 mm;

[0108] 640 parts of recycled coarse aggregate with a particle size of 10-20 mm;

[0109] 42 parts of polyacrylate emulsion;

[0110] 3 parts of polyacrylonitrile fiber;

[0111] 1.5 parts of high performance water reducing agent;

[0112] 1 part defoamer.

[0113] The dry matter in the emulsion of the polyacrylate emulsion is 18 parts, and the water contained in the polyacrylate emulsion is included in the total water consumption.

[0114] The fine aggregate is natural medium sand in Zone II with a fineness modulus of 2.5; the recycled coarse aggregate used is continuously graded and the raw material is waste concrete.

[0115] The method for preparing polyacrylate-modified recycled concrete comprises the following steps:

[0116] Step 1: Vacuum saturation treatment of recycled aggregate, the steps are as follows:

[0117] Step a: Put the recycled aggregate into a sealable container with a vacuum pump and a water injection pipe;

[0118] Step b: Start the vacuum pump, reduce the absolute pressure in the container to 2 kPa within 15 minutes and maintain the vacuum for 4 hours;

[0119] Step c: While maintaining the vacuum, inject mixing water into the container. The mixing water should completely submerge the recycled aggregate;

[0120] Step d: After the recycled aggregate is submerged in the mixing water, the vacuum is maintained for 2 hours, normal pressure is restored, and the immersion is continued for 24 hours until the polyacrylate-modified recycled concrete begins to be prepared;

[0121] Step e: soaking the recycled aggregate after vacuum saturation treatment in mixing water for later use;

[0122] Step 2: Mix all the mixing water, polyacrylate emulsion and silicone defoamer according to the above-mentioned proportion, stir evenly by mechanical or manual means to prepare a mixed solution for standby use;

[0123] Step 3: Mix all the polyacrylonitrile fibers, all the sand and 45% of cement according to the above-mentioned mix ratio, and dry-mix them evenly by mechanical or manual means to prepare a mixed dry material for standby use;

[0124] Step 4: Take the recycled aggregate pretreated in step 1 out of the water and place it on a screen or grate for drainage. The degree of drainage is when the recycled aggregate reaches a saturated surface dry state, that is, when there is no water dripping from the bottom and the surface of the recycled aggregate is not completely dry, weigh it according to the above mix ratio, and immediately proceed to the next step of preparing polyacrylate-modified recycled concrete after weighing;

[0125] Step 5: Weigh 55% of the cement according to the above mix ratio and put it into the forced mixer, and weigh 45% of the mixed solution prepared in step 2 and put it into the mixer, stir at 50r / min for 60s, stop the mixer, and then add all the recycled coarse aggregate weighed in step 4, continue stirring for 40s and then stop;

[0126] Step 6: After step 5 is completed and the machine is shut down, all the mixed dry materials prepared in step 3 are immediately put into the mixer, stirred at a speed of 50r / min for 40s and then shut down;

[0127] Step 7: Mix all the high-performance water-reducing agent weighed according to the above-mentioned mix ratio with the remaining 55% of the mixed solution prepared in step 2, stir them evenly by mechanical or manual means, put them into the mixer after stopping the machine in step 6, start stirring at a speed of 50r / min for 120s, and discharge the materials after stopping the machine to obtain the polyacrylate-modified recycled concrete of the present invention.

[0128] Example 4

[0129] Polyacrylate modified recycled concrete, the recycled concrete includes the following components in parts by weight:

[0130] Mix 185 parts of water;

[0131] 430 parts of cement;

[0132] 680 parts of fine aggregate;

[0133] 425 parts of recycled coarse aggregate with a particle size of 5-10 mm;

[0134] 670 parts of recycled coarse aggregate with a particle size of 10-20 mm;

[0135] 49 parts of polyacrylate emulsion;

[0136] 5 parts of polyacrylonitrile fiber;

[0137] 2 parts of high performance water reducing agent;

[0138] 1.5 parts of defoaming agent.

[0139] The dry matter in the emulsion of polyacrylate emulsion is 21 parts, and the water contained in the polyacrylate emulsion is included in the total water consumption.

[0140] The fine aggregate is natural medium sand in Zone II with a fineness modulus of 2.5; the recycled coarse aggregate used is continuously graded and the raw material is waste concrete.

[0141] The method for preparing polyacrylate-modified recycled concrete comprises the following steps:

[0142] Step 1: Vacuum saturation treatment of recycled aggregate, the steps are as follows:

[0143] Step a: Put the recycled aggregate into a sealable container with a vacuum pump and a water injection pipe;

[0144] Step b: Start the vacuum pump, reduce the absolute pressure in the container to 3 kPa within 15 minutes and maintain the vacuum for 4 hours;

[0145] Step c: While maintaining the vacuum, inject mixing water into the container. The mixing water should completely submerge the recycled aggregate;

[0146] Step d: After the recycled aggregate is submerged in the mixing water, the vacuum is maintained for 2 hours, normal pressure is restored, and the immersion is continued for 22 hours until the polyacrylate-modified recycled concrete begins to be prepared;

[0147] Step e: soaking the recycled aggregate after vacuum saturation treatment in mixing water for later use;

[0148] Step 2: Mix all the mixing water, polyacrylate emulsion and silicone defoamer according to the above-mentioned proportion, stir evenly by mechanical or manual means to prepare a mixed solution for standby use;

[0149] Step 3: Mix all the polyacrylonitrile fibers, all the sand and 50% of the cement according to the above-mentioned mix ratio, and dry-mix them evenly by mechanical or manual means to prepare a mixed dry material for standby use;

[0150] Step 4: Take the recycled aggregate pretreated in step 1 out of the water and place it on a screen or grate for drainage. The degree of drainage is when the recycled aggregate reaches a saturated surface dry state, that is, when there is no water dripping from the bottom and the surface of the recycled aggregate is not completely dry, weigh it according to the above mix ratio, and immediately proceed to the next step of preparing polyacrylate-modified recycled concrete after weighing;

[0151] Step 5: Weigh 50% of the cement according to the above mix ratio and put it into the forced mixer, and weigh 45% of the mixed solution prepared in step 2, stir at 50r / min for 80s, stop the machine, and then add all the recycled coarse aggregate weighed in step 4, continue stirring for 30s and then stop;

[0152] Step 6: After step 5 is completed and the machine is shut down, all the mixed dry materials prepared in step 3 are immediately put into the mixer and stirred at a speed of 50 r / min for 30 seconds before shutting down;

[0153] Step 7: Mix all the high-performance water-reducing agent weighed according to the above-mentioned mix ratio with the remaining 55% of the mixed solution prepared in step 2, and stir them evenly by mechanical or manual means. After stopping the machine in step 6, put them into the mixer and stir them at a speed of 50 r / min for 120 seconds. After stopping the machine, the polyacrylate-modified recycled concrete of the present invention is obtained by discharging the material.

[0154] Performance Indicators

[0155] In order to show that the present invention has strong durability and to show the superiority of its performance index compared with the existing ordinary concrete and recycled aggregate concrete, the research and development team designed a sulfate-freeze-thaw coupling cycle test. The three groups of specimens are ordinary concrete (Group F1), recycled concrete (Group F2) and polyacrylate modified recycled concrete (Group F3). The mix proportions of the three groups of specimens are shown in the table below. The test uses a 5% Na2SO4 solution as the erosion liquid. The freeze-thaw process is carried out with reference to the quick freezing method in GB / T 50082-2009 "Standard for Test Methods for Long-term Performance and Durability of Ordinary Concrete". After the specimens are formed, they are cured for 24 days under standard curing conditions and then immersed in a 5% Na2SO4 erosion liquid until they reach 28 days old. On the 28th day, the initial mass, dynamic elastic modulus, flexural and compressive strength of the three groups of specimens were tested respectively, and then the salt-freeze coupling test process was entered. The specimens were placed in the rubber barrel of the rapid freeze-thaw testing machine and 5% Na2SO4 erosion liquid was injected. The erosion liquid was 5 mm higher than the top of the specimen. The outside of the rubber barrel was filled with antifreeze liquid. The mass loss and dynamic elastic modulus were measured once every 25 salt-freeze cycles, and the flexural and compressive strengths were measured once every 50 salt-freeze cycles. The broken specimens continued to be placed in the rubber barrel to maintain the consistency of the internal environment of the salt-freeze test chamber.

[0156] Table 1 shows the mix ratios of the three groups of specimens.

[0157]

[0158] Table 1

[0159] The experimental results are as follows Figure 1-4 As shown,

[0160] The results show that:

[0161] (1) After the 100th salt-freezing cycle, the relative dynamic elastic modulus of ordinary concrete and recycled concrete were both lower than 60%, 56.3% and 47.5% respectively. At this time, the relative dynamic elastic modulus of polyacrylate-modified recycled concrete was still as high as 82.7%, indicating that the dynamic elastic modulus loss rate of polyacrylate-modified recycled concrete in salt-freezing cycle was the lowest;

[0162] (2) The mass loss rates of the three groups of specimens under 200 salt-freezing cycles were all less than 5%, indicating that the mass loss rate index is less sensitive in evaluating the anti-salt-freezing coupling effect of concrete, but the mass loss rate of polyacrylate-modified recycled concrete is the lowest;

[0163] (3) The results of mechanical properties tests show that when the number of salt-freezing cycles is the same, the loss rate of compressive and flexural strength of recycled concrete is the highest, followed by ordinary concrete, and the loss rate of polyacrylate-modified recycled concrete is the lowest.

[0164] In addition, the invention team established a concrete structure life prediction model and fitted the relative dynamic elastic modulus curve. They selected Tibet Linzhi (Southwest), Gansu Jiuquan (Northwest), Inner Mongolia Hohhot (North China) and Jilin Changchun (Northeast) as examples of concrete application locations with representative salt-freezing environments in my country, and predicted the service life of three types of concrete. The data fitting process, life prediction model establishment process and life prediction results are as follows:

[0165] Table 2 Relative dynamic elastic modulus data fitting

[0166]

[0167] Table 2

[0168] Based on the existing concrete life model in the experiment of the present invention, combined with the practice and research on the quantification of concrete service life, the concrete salt freezing service life model is expressed as:

[0169]

[0170] In the formula: T represents the service life of concrete in salt-freezing environment; K represents the salt-freezing cycle life (number of times) of concrete in the test room; S represents the number of salt-freezing cycles in the test room equivalent to the number of salt-freezing cycles under natural conditions; M represents the annual average number of freeze-thaw cycles suffered by the concrete in a winter climate in the service area.

[0171] Under the condition of freeze-thaw single factor cycle, S usually takes a value of 10-15. The experiment in the present invention takes into account that the sulfate-freeze-thaw cycle is in a highly coupled state under indoor conditions, and S takes an upper limit value of 15.

[0172] After calculation, the service life prediction results of the three types of concrete are shown in the following table

[0173] Table 3 Prediction of concrete durability service life under salt-freezing environment

[0174]

[0175] Table 3

[0176] It can be seen from the data in the above table that the service life of the polyacrylate-modified recycled concrete, which is the object of the present invention, is 17.0 years higher than that of ordinary concrete and 19.6 years higher than that of recycled aggregate concrete in areas of China such as Southwest, Northwest, North China and Northeast China where salt frost erosion is more serious.

[0177] It should be understood by those skilled in the art that the embodiments of the present invention described above and shown in the accompanying drawings are only examples and do not limit the present invention, and the purpose of the present invention has been fully and effectively achieved. The functional and structural principles of the present invention have been demonstrated and explained in the embodiments, and the embodiments of the present invention may be deformed or modified in any way without departing from the principles.

Claims

1. A method for preparing polyacrylate-modified recycled concrete, characterized in that: The components of the polyacrylate modified recycled concrete in parts by weight are: 170-200 parts of mixing water; 350-500 parts of cement; 500-800 parts of fine aggregate; 300-500 parts of recycled coarse aggregate with a particle size of 5-10 mm; 500-800 parts of recycled coarse aggregate with a particle size of 10-20 mm; 35-55 parts of polyacrylate emulsion; 1-5 parts of polyacrylonitrile fiber; 1-5 parts of high-performance water reducing agent; and 1-3 parts of defoaming agent, and the steps are as follows: Step 1: Vacuum saturation treatment of recycled coarse aggregate, the steps are as follows: Step a: Put the recycled coarse aggregate into a sealable container with a vacuum pump and a water injection pipe; Step b: Start the vacuum pump, reduce the absolute pressure in the container to 1-5 kPa within 10-15 minutes and maintain the vacuum for 3-4 hours; Step c: While maintaining the vacuum degree, inject mixing water into the container, and the mixing water should completely submerge the recycled coarse aggregate; Step d: After the recycled coarse aggregate is submerged in the mixing water, the vacuum is maintained for 1-2 hours, normal pressure is restored, and the immersion is continued for no less than 18 hours; Step e: soaking the recycled coarse aggregate after vacuum saturation treatment in mixing water for later use; Step 2: Mix all the mixing water, polyacrylate emulsion and silicone defoamer according to the above-mentioned proportion, stir evenly by mechanical or manual means to prepare a mixed solution for standby use; Step 3: Mix all the polyacrylonitrile fibers, all the sand and 45-50% of cement according to the above-mentioned mix ratio, and dry-mix them evenly by mechanical or manual means to prepare a mixed dry material for standby use; Step 4: Take out the recycled coarse aggregate pretreated in step 1 from the water, drain it, weigh it according to the above mix ratio, and immediately proceed to the next step of preparing polyacrylate-modified recycled concrete after weighing; Step 5: Weigh 50-55% of the cement according to the above mix ratio and put it into the forced mixer, and weigh 40-45% of the mixed liquid prepared in step 2, put it into the mixer, stir, stop the mixer, and then put in all the recycled coarse aggregate weighed in step 4, continue stirring, and stop; Step 6: After step 5 is completed and the machine is stopped, all the mixed dry materials obtained in step 3 are immediately put into the mixer, and the machine is started and stirred and then stopped; Step 7: Mix all the high-performance water-reducing agent weighed according to the above-mentioned mix ratio with the remaining 55-60% of the mixed liquid prepared in step 2, stir them evenly by mechanical or manual means, put them into the mixer after stopping the machine in step 6, stir them, and then the polyacrylate-modified recycled concrete is obtained after stopping and discharging the materials.

2. The method for preparing polyacrylate-modified recycled concrete according to claim 1, characterized in that: In step 4, the recycled coarse aggregate is placed on a sieve or a grate for drainage, and the degree of drainage is that the recycled coarse aggregate reaches a saturated surface dry state, that is, it is weighed when there is no water dripping from the bottom and the surface of the recycled coarse aggregate is not completely dry.

3. The method for preparing polyacrylate-modified recycled concrete according to claim 1, characterized in that: In the step 5, 50-55% of the cement weight according to the mix ratio and 40-45% of the mixed solution prepared in step 2 are added to the mixer and stirred at a speed of 47-55 r / min for 60-90 seconds, then the mixer is stopped. Then, the recycled coarse aggregate is added and stirred for 30-50 seconds before stopping.

4. The method for preparing polyacrylate-modified recycled concrete according to claim 1, characterized in that: In the step 6, all the mixed dry materials obtained in the step 3 are put into the mixer, and the mixer is stirred at a speed of 47-55 r / min for 30-50 seconds and then stopped.

5. The method for preparing polyacrylate-modified recycled concrete according to claim 1, characterized in that: After the mixer is put into the step 7, the mixer is started and stirred at a speed of 47-55 r / min for 120-150 s, and the material is discharged after the mixer is stopped.

6. The method for preparing polyacrylate-modified recycled concrete according to claim 1, characterized in that: The dry matter in the polyacrylate emulsion is 15-25 parts, and the water contained in the polyacrylate emulsion should be included in the total water consumption.

7. The polyacrylate modified recycled concrete according to claim 1, characterized in that: The fine aggregate is natural medium sand in zone II with a fineness modulus of 2.5; the recycled coarse aggregate used is continuously graded, and the raw material is waste concrete.

Citation Information

Patent Citations

  • High-performance concrete containing recycled aggregate and preparation method thereof

    CN110713361A